Analysis of Pharmacovigilance Databases for Dolutegravir Safety in Pregnancy. (9th October 2019) - van De Ven, Nikolien S; Pozniak, Anton L; Levi, Jacob A; Clayden, Polly; Garratt, Anna; Redd, Christopher; Mofenson, Lynne M; Hill, Andrew
Abstract: Background: The Botswana Tsepamo study reported neural tube defects (NTDs) in 4 of 426 (0.94%) infants of women receiving preconception dolutegravir (DTG) antiretroviral therapy (ART) vs 14 of 11 300 (0.12%) receiving preconception non-DTG ART. Data are needed to investigate this potential safety signal. Clinicians, patients, and pharmaceutical companies can report adverse drug reactions (ADRs) to pharmacovigilance databases. Data from ADRs reported to various pharmacovigilance databases were searched for NTDs. Methods: Four pharmacovigilance databases (World Health Organization [WHO] VigiAccess; United Kingdom Medicines Health Regulatory Authority [UK MHRA]; European Medicines Agency [EMA] EudraVigilance; US Food and Drug Administration Adverse Event Reporting System [FAERS]) with online data availability were analyzed for NTD reports for 4 integrase inhibitors (DTG, raltegravir, elvitegravir, bictegravir), 2 protease inhibitors (darunavir, atazanavir), and 2 nonnucleoside reverse transcriptase inhibitors (nevirapine, efavirenz). Reports in the system organ class "congenital or familial disorders" were searched for NTDs. Results: NTDs have been reported among infants born from women taking a wide range of antiretrovirals in 4 pharmacovigilance databases (WHO VigiAccess, 116 reactions; UK MHRA, 8 cases; EMA EudraVigilance, 20 cases; FAERS, 44 cases). Six NTDs were identified for DTG across the pharmacovigilance databases. Cases were very hard to interpret, given the lack of clear denominators. Conclusions: Pharmacovigilance databases have many limitations, most importantly lack of a clear denominator for patients exposed to the drug of interest and duplicate cases that are difficult to identify. Given widespread use of new antiretroviral drugs worldwide and anticipated use of new drugs, prospective follow-up of pregnant women and birth surveillance studies such as Tsepamo are critically needed. Abstract : Neural tube defects have been reported among infants born from women taking a wide range of antiretrovirals in 4 pharmacovigilance databases. Safety reports were inconsistent between databases and very hard to interpret